Hericium erinaceus Compound Beverage and Its Ameliorative Effect on Alcohol-induced Oxidative Injury in Rats - Wenfang ZHANG; Chenglin WU; Huan NING; Zhuanzhuan LI; Liying ZHAI; Haoran YANG; Jing WANG; Xuyuan ZHANG; Nan QIN (Shipin gongye ke-ji)
Objective: To develop a Hericium erinaceus beverage and investigate its protective effect on alcohol-induced gastric mucosa injury in vivo. The antioxidant properties were possessed by H. erinaceus, and the gastrointestinal tract was protected. Methods: Using H. erinaceus extract as the main raw material, and hawthorn and orange peel extract as auxiliary material, the formulation and clarifying process of the compound beverage was optimized using single factor experiments combined with the orthogonal test and Box-Behnken response surface method. Physical and chemical tests were also conducted. Simultaneously, an alcohol oxidative injury model was established by 50% alcohol administration in rats. The protective effects of the water extract of H. erinaceus on oxidative damage in rats were assessed. Results: The optimal ingredient ratio of the H. erinaceus beverage was 23% H. erinaceus, 37% hawthorn, and 14% orange peel water extracts, and 21% of 30% xylitol, and 5% of a 1% citric acid and sodium citrate (2:1) solutions. Based on the optimization results of univariate experiments, the optimal clariﬁcation process parameters of the H. erinaceus beverage were obtained using orthogonal experiments: Clariﬁcation temperature 25 ℃, clariﬁcation time 80 min, gelatin dosage 2 g/L, and sodium carboxymethyl cellulose dosage 0.15 g/L. Under these process conditions, good stability was exhibited by the product, and a light transmittance of 96.1% was achieved by the H. erinaceus beverage after clarification. The physical and chemical indicators (soluble solid: 30 g/L, reducing sugar: 0.2733 g/L, total phenolic: 6.73%, and pH: 3.74) of the beverage produced using the optimized process were found to meet the requirements of GB/T 31326 "Plant based beverages", and practical significance was demonstrated by the final formula. Animal tests showed that the H. erinaceus water extract can substantially ameliorate alcoholic oxidative damage in rats. HE staining of gastric tissue showed that the gastric mucosa of the model group was exfoliated, with a disordered glandular structure, enlarged tissue space, and severely ulcerated gastric tissue. After administration of the H. erinaceus water extract, the structure of gastric tissue cells was neater than that of the model group, and the degree of swelling and bleeding was reduced. Compared with the model group, increases in T-AOC, GSH, and CAT levels in serum and gastric tissue were observed with the H. erinaceus water extract, and significant increases in T-AOC level in serum, as well as GSH and T-AOC levels in gastric tissue, were detected. Simultaneously, the H. erinaceus water extract compound significantly reduced the NO and MPO levels, as well as the NO level in gastric tissue. Conclusion: The H. erinaceus beverage preparation process was demonstrated to be feasible. Good antioxidant activity was exhibited by the H. erinaceus beverage, and alcohol-induced gastric mucosa injury was shown to be improved in vivo.